THE EFFECTIVENESS OF PEER TUTORING IN TEACHING SPEAKING - Anam, Mukhtarul (Universitas PGRI Sumatera Barat, 2020)
Learning a language provides some aspects such as speaking, writing, reading and listening. This research is to know the different students’ mean score studying by using peer tutoring and teacher tutoring in learning speaking. Experimental research is used This research. The subjects of the research are VIII grade students of junior high school Sunan Santri Babat Lamongan. The sample in the research is 40 students providing 20 students of VIII B as the experimental groupand 20 students of VIII A as the control group. The research instruments consist of pre- test, and post-test. In the research findings, it is concluded that the use of peer tutoring is more effective for learning speaking than teacher tutoring. The researcher gives suggestions that peer tutoring is effective in teaching speaking because students can improve their ability and share with the groups. For the next researcher, it is suggested to carry out a research in the same study but in other places and subjects of the study